Pencirian Debit Aliran Sungai Citarum Hulu - Yayat Hidayat; Kukuh Murtilaksono; Enni Dwi Wahjunie; Diah Retno Panuju (Jurnal Ilmu Pertanian Indonesia, 2013)
Citarum is one of strategic rivers in West Java. In the upper part of this river, there are 3 large dams (Saguling, Cirata, and Jatiluhur) which operates hydroelectric power that supply ± 20% electricity needs of Java-Bali area. Run off discharge of the river are fluctuating widely so greatly affect the performance of electricity production, supply of irrigation, and household water in the downstream area. The research aims to identify character of river discharge of Citarum Hulu and its relation with land use changes and farm management. River discharge were analyzed at the inlet of Saguling dam in Kampung Nanjung and some stream monitoring stations located in Ciwidey, Cisangkuy, and Cikapundung-Gandok. River discharge was highly fluctuating. In the peak of rainy season the flow rate can reach 578 m3/sec which caused flooding in several area such as Majalaya, Banjaran, and Dayeuhkolot. In contrary, in dry season the flow was very low, about 2.7 m3/sec, causing drought, failure of rice harvest, and reduced water supply to hydropower plant of Saguling. In addition to affecting rainfall patterns, the flow rate fluctuations was also influenced by pattern of land use and management. Land utilization that was not in accordance with the land capability was the main cause of land degradation which in turn would decrease hydrology function of watershed to control river discharge in rainy season.